A kind of building material containing waste and preparation method thereof

By combining desulfurized gypsum, phosphogypsum, composite fibers and mineral admixtures, and adding admixtures such as waterproofing agents, a building material with high water resistance and strength is prepared, which solves the problem of water resistance of existing gypsum-based self-leveling mortars. The problem of insufficient sex and strength.

CN118908687BActive Publication Date: 2025-01-24TIANJIN JUSHI TECH DEV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411415135.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-24
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing gypsum-based self-leveling mortar has problems such as poor water resistance and low strength, which limits its application range.

Method used

Adopt a building material containing waste, combine desulfurization, phospholosypsum, composite fiber and mineral doping materials, and add waterproofing agents, water preservation agents and other exterior agents to prepare building materials with water resistance and strength. Essence

Benefits of technology

Significantly improves the compressive strength, flexural strength and water resistance of building materials, extends the service life in humid environments, and enhances the structural stability and toughness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, in particular to a building material containing waste and a preparation method thereof. The building material comprises the following weight components: 25-35 parts of desulfurized gypsum, 10-15 parts of phosphogypsum, 15-25 parts of mineral admixtures, 30-40 parts of steel slag powder, 15-25 parts of tailings sand, 10-20 parts of carbide slag, 0.2-1.0 parts of composite fiber, 0.3-0.8 parts of waterproofing agent, 0.05-0.10 parts of water retaining agent, 0.5-1.0 parts of redispersible latex powder, 0.1-0.3 parts of water reducing agent, 0.1-0.5 parts of air entraining agent, and 10-15 parts of water. The building material containing waste prepared by the present invention has excellent mechanical properties and excellent water resistance, thereby extending its service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a building material containing waste and a preparation method thereof. Background Art

[0002] With the rapid development of economy and the acceleration of urbanization, the demand for materials in the construction industry is increasing, which is accompanied by the generation of a large amount of solid waste. The rational treatment and reuse of waste has become one of the important challenges facing the current construction industry.

[0003] Desulfurization gypsum is a solid waste produced in the wet desulfurization process of coal-fired power plants. Its main component is calcium sulfate dihydrate. Gypsum-based self-leveling mortar has the advantages of easy construction, high early strength, fireproof and soundproof. It can not only effectively alleviate the environmental pollution caused by desulfurization gypsum, but also provide a new type of building material. However, at present, gypsum-based self-leveling mortar has the problems of poor water resistance and low strength, which greatly restricts its application scope.

[0004] Therefore, we propose a building material containing waste and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a building material containing waste and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A building material containing waste comprises the following components by weight: 25-35 parts of desulfurized gypsum, 10-15 parts of phosphogypsum, 15-25 parts of mineral admixtures, 30-40 parts of steel slag powder, 15-25 parts of tailings sand, 10-20 parts of carbide slag, 0.2-1.0 parts of composite fiber, 0.3-0.8 parts of waterproofing agent, 0.05-0.10 parts of water retaining agent, 0.5-1.0 parts of redispersible latex powder, 0.1-0.3 parts of water reducing agent, 0.1-0.5 parts of air entraining agent and 10-15 parts of water.

[0008] Furthermore, the mineral admixture includes the following components by weight: 25-35 parts of fly ash, 40-50 parts of slag powder, 15-25 parts of CFB slag, 10-20 parts of red mud, and 0.05-0.08 parts of grinding aid.

[0009] Furthermore, the preparation method of the composite fiber is as follows:

[0010] Step S1: evenly mix concentrated nitric acid, deionized water and ammonium cerium nitrate to obtain an acidic ammonium cerium nitrate solution; evenly mix deionized water, polyvinyl alcohol fiber and glycidyl methacrylate, dropwise add the acidic ammonium cerium nitrate solution for 30-50 minutes, react at 40-50° C. for 4-6 hours, filter, wash and dry to obtain epoxidized polyvinyl alcohol fiber;

[0011] Step S2: heating the basalt fiber at 250-300° C. for 1-2 hours, cooling to room temperature, soaking in an acetone solution for 1-2 hours, washing and drying to obtain pretreated basalt fiber; uniformly mixing the pretreated basalt fiber with anhydrous ethanol, deionized water and 3-aminopropyltrimethoxysilane, adding nano-silica, reacting at 55-65° C. for 4-6 hours, filtering, washing and drying to obtain amino basalt fiber;

[0012] Step S3: Evenly mix the epoxidized polyvinyl alcohol fiber, the amino basalt fiber and tetrahydrofuran, react for 4-6 hours, and obtain composite fibers after filtering, washing and drying.

[0013] Furthermore, in step S1, the concentration of concentrated nitric acid is 16 mol / L, and the mass ratio of concentrated nitric acid, deionized water and cerium ammonium nitrate is 1:(10-12):(0.4-0.5).

[0014] Furthermore, in step S1, the mass ratio of deionized water, polyvinyl alcohol fiber, glycidyl methacrylate and acidic ammonium cerium nitrate solution is (32-36):1:(2.0-2.5):(4.0-4.2).

[0015] Furthermore, in step S2, the mass ratio of the pretreated basalt fiber and anhydrous ethanol, deionized water, and 3-aminopropyltrimethoxysilane is 1:(10-12):(2-3):(0.2-0.4), and the mass of nano-silicon dioxide is 15-25% of the mass of 3-aminopropyltrimethoxysilane.

[0016] Furthermore, in step S3, the mass ratio of the epoxidized polyvinyl alcohol fiber, the amino basalt fiber and tetrahydrofuran is 1:(1-2):(4-6).

[0017] Furthermore, the preparation method of the waterproofing agent is as follows:

[0018] Step (1): mix carboxymethyl chitosan and deionized water evenly, add methacrylic anhydride, react at 55-65°C for 3-5h, dialyze and dry to obtain double-bond carboxymethyl chitosan;

[0019] Step (2): Evenly mix the epoxy-terminated silicone oil and isopropanol, add N-aminoethyl-3-aminopropyltriethoxysilane, react at 45-55°C for 1-3h, add ethyl orthosilicate, hexadecanetriethoxysilane and deionized water, continue to react for 2-4h, heat to 70-80°C, add double-bond carboxymethyl chitosan and tetrabutylammonium bromide, react for 4-6h, cool to 45-55°C, add sodium hydroxide, continue to react for 2-3h, wash and distill under reduced pressure to obtain a double bond-containing compound;

[0020] Step (3): uniformly mix octylphenol polyoxyethylene ether, alcohol ether carboxylate and deionized water, add styrene, butyl acrylate, methyl methacrylate and acrylic acid, stir for 20-30 minutes, adjust the system pH to 8-10 with sodium hydroxide solution, heat to 70-80°C, drip initiator aqueous solution, drip for 40-60 minutes, keep warm for reaction for 1-2 hours, cool to 50-60°C, add double bond-containing compound, keep warm for reaction for 0.5-1.0 hours, and obtain a waterproofing agent.

[0021] In the above technical scheme, the amino group in carboxymethyl chitosan and methacrylic anhydride undergo amidation reaction to obtain double-bond carboxymethyl chitosan; the epoxy group at one end of the terminal epoxy silicone oil structure undergoes a ring-opening reaction with the amino group in N-aminoethyl-3-aminopropyltriethoxysilane, followed by a hydrolysis and polycondensation reaction with ethyl orthosilicate and hexadecanetriethoxysilane to introduce hydrophobic long-chain alkyl and low surface energy polysiloxane segments; under the action of a catalyst, the abundant hydroxyl and carboxyl groups on the double-bond carboxymethyl chitosan react with the terminal epoxy silicone oil structure to form a polysiloxane segment. The epoxy group at the other end undergoes a ring-opening reaction to introduce a double bond to obtain a double bond-containing compound; finally, using styrene, butyl acrylate, methyl methacrylate, acrylic acid and a double bond-containing compound as raw materials, an emulsion polymerization is performed to obtain a waterproofing agent, which can form a solid hydrophobic film on the surface of the desulfurized gypsum crystals, inhibit the growth of the desulfurized gypsum crystals, and increase the water resistance of the desulfurized gypsum; at the same time, the carboxylic acid group in the structure of the double bond-containing compound can form a strong chemical bond with the desulfurized gypsum, thereby improving the adhesion of the waterproofing agent and further improving the water resistance effect.

[0022] Furthermore, in the step (1), the mass ratio of carboxymethyl chitosan, deionized water and methacrylic anhydride is 1: (30-50): (0.15-0.20).

[0023] Furthermore, in step (2), the mass ratio of the epoxy-terminated silicone oil, isopropyl alcohol, and N-aminoethyl-3-aminopropyltriethoxysilane is 1:(4-6):(0.03-0.05), and the mass of ethyl orthosilicate is 0.5-0.7 times the mass of N-aminoethyl-3-aminopropyltriethoxysilane.

[0024] Furthermore, in the step (2), the mass ratio of ethyl orthosilicate, hexadecanetriethoxysilane and deionized water is 1:(1.0-1.5):(3-4).

[0025] Furthermore, in the step (2), the mass ratio of the epoxy-terminated silicone oil, the double-bond carboxymethyl chitosan, tetrabutylammonium bromide and sodium hydroxide is 1: (1-2): (0.1-0.3): (1.5-2.0).

[0026] Furthermore, in the step (3), the mass ratio of octylphenol polyoxyethylene ether, alcohol ether carboxylate and deionized water is 1: (0.20-0.25): (50-60).

[0027] Furthermore, in step (3), the mass ratio of styrene, butyl acrylate, methyl methacrylate, acrylic acid and the double bond-containing compound is 1:(1-2):(2-3):(0.5-1.0):(1.5-2.5).

[0028] Furthermore, the concentration of the initiator aqueous solution is 2-5wt%, and the amount thereof is 4-6 times the mass of styrene.

[0029] Furthermore, the initiator is azobisisobutyronitrile.

[0030] Furthermore, the water-retaining agent is hydroxypropyl methylcellulose ether.

[0031] Furthermore, the water reducer is a polycarboxylate water reducer.

[0032] Furthermore, the air entraining agent is a sodium rosin acid air entraining agent.

[0033] A building material containing waste and a preparation method thereof, comprising the following steps:

[0034] The mineral admixture, steel slag powder, tailings sand and carbide slag are mixed evenly, and desulfurized gypsum, phosphogypsum, composite fiber and water are added and mixed evenly to obtain a mixture; the mixture and a water retaining agent, a dispersant, a water reducing agent, an air entraining agent and a waterproofing agent are mixed evenly to obtain a building material containing waste.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. A waste-containing building material and a preparation method thereof of the present invention, wherein epoxidized polyvinyl alcohol fiber is obtained by grafting glycidyl methacrylate on the surface of polyvinyl alcohol fiber, thereby enhancing the chemical activity of the polyvinyl alcohol fiber; then, the surface of basalt fiber is modified by using a composite liquid of nano-silicon dioxide and 3-aminopropyltrimethoxysilane to obtain amino basalt fiber, thereby increasing the surface roughness of basalt fiber and improving the bonding force between basalt fiber and substrate; finally, the epoxidized polyvinyl alcohol fiber and the amino basalt fiber are mixed to obtain composite fiber, which can not only improve the compressive strength and flexural strength of mortar and enhance its structural stability, but also improve the water resistance of gypsum, so that it maintains good physical properties in a humid environment and prolongs its service life. In addition, the use of composite fiber can also improve the durability of gypsum, resist cracks and damage in long-term use, and improve the overall performance and reliability of building materials.

[0037] 2. A waste-containing building material and a preparation method thereof of the present invention uses desulfurized gypsum and phosphogypsum as main cementitious materials, steel slag and tailings sand as aggregates, carbide slag as alkali activator, fly ash, slag powder, CFB slag and red mud as mineral admixtures, and adds composite fiber, admixtures (including waterproofing agent, water retaining agent, redispersible latex powder, water reducing agent and air entraining agent) and water to obtain environmentally friendly mortar, that is, a waste-containing building material, which not only significantly improves the compressive strength and flexural strength of the mortar, enhances the structural stability and toughness of the mortar, overcomes the brittleness of traditional gypsum materials, and enables it to better withstand external loads; at the same time, it improves the water resistance of the mortar, reduces the risk of moisture penetration and dissolution, and thus extends the service life of the mortar in a humid environment. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In this embodiment, the desulfurized gypsum is β-type semi-hydrated desulfurized gypsum; phosphogypsum is semi-hydrated phosphogypsum, which is sourced from Anhui Senke New Materials Co., Ltd.; steel slag powder is 40-70 mesh in size, which is sourced from Shijiazhuang Zhengyu New Materials Technology Co., Ltd.; tailings sand is 40-70 mesh in size, which is sourced from Qingdao Shuntianda Mining Co., Ltd.; fly ash is first-class fly ash, with a particle size of 200-300 mesh, which is sourced from Jining Hengzhi New Building Materials Co., Ltd.; calcium carbide slag is 200 mesh in size, which is sourced from Gongyi Qianghong Water Purification Materials Co., Ltd.; polyvinyl alcohol fiber is 12 mm in length and 5 μm in diameter of a single filament, which is sourced from Nanjing Pioneer Technology Industry Co., Ltd.; basalt fiber is 9 mm in length and 15 μm in diameter of a single filament, which is sourced from Tai'an Songze Composite Materials Co., Ltd.; water reducer is polycarboxylic acid water reducer, model PC-1030; slag powder is S95 grade slag powder, which is sourced from Shandong Kefa Building Materials Co., Ltd.; CFB slag is 180 m3 in specific surface area after passing through a 0.15 mm sieve. 2 / kg, sourced from Shanxi Datuhe Coal-fired Power Plant; red mud: particle size is 325 mesh, sourced from Lingshou Yixin Mineral Products Processing Plant; grinding aid: "Tonghui" brand TH-2B cement grinding aid; nano-silica: water-based nano-SiO2, particle size is 20nm; end-epoxy silicone oil: model E875446, sourced from Shanghai MacLean Biochemical Technology Co., Ltd.

[0040] In the following examples and comparative examples, 1 part is equal to 100 g.

[0041] Embodiment 1: A method for preparing a building material containing waste, comprising the following process:

[0042] 15 parts of fly ash, 40 parts of slag powder, 15 parts of CFB slag, 10 parts of red mud and 0.05 parts of grinding aid are mixed evenly to obtain a mineral admixture; 15 parts of mineral admixture, 30 parts of steel slag powder, 15 parts of tailings sand and 10 parts of carbide slag are mixed evenly, and 25 parts of desulfurized gypsum, 10 parts of phosphogypsum, 0.2 parts of composite fiber and 10 parts of water are added and mixed evenly to obtain a mixture; the mixture and 0.05 parts of water retaining agent, 0.5 redispersible latex powder, 0.1 parts of water reducing agent, 0.1 parts of air entraining agent and 0.3 parts of waterproofing agent are mixed evenly to obtain a building material containing waste;

[0043] The preparation method of the composite fiber is as follows:

[0044] Step S1: 0.1 parts of 16 mol / L concentrated nitric acid, 1 part of deionized water and 0.04 parts of ammonium cerium nitrate are mixed evenly to obtain an acidic ammonium cerium nitrate solution; 3.2 parts of deionized water, 0.1 parts of polyvinyl alcohol fiber and 0.2 parts of glycidyl methacrylate are mixed evenly, 0.4 parts of the acidic ammonium cerium nitrate solution is added dropwise for 30 minutes, the mixture is reacted at 40° C. for 4 hours, and after filtering, washing and drying, epoxidized polyvinyl alcohol fiber is obtained;

[0045] Step S2: heating 0.1 parts of basalt fiber at 250° C. for 1 hour, cooling to room temperature, soaking in an acetone solution for 1 hour, washing and drying to obtain pretreated basalt fiber; uniformly mixing 0.1 parts of pretreated basalt fiber with 1 part of anhydrous ethanol, 0.2 parts of deionized water, and 0.02 parts of 3-aminopropyltrimethoxysilane, adding 0.003 parts of nano-silicon dioxide, reacting at 55° C. for 4 hours, filtering, washing, and drying to obtain amino basalt fiber;

[0046] Step S3: 0.1 parts of epoxidized polyvinyl alcohol fiber, 0.1 parts of amino basalt fiber and 0.4 parts of tetrahydrofuran are mixed evenly, reacted for 4 hours, filtered, washed and dried to obtain composite fibers;

[0047] The preparation method of the waterproofing agent is as follows:

[0048] Step (1): 0.3 parts of carboxymethyl chitosan and 9 parts of deionized water were mixed evenly, 0.045 parts of methacrylic anhydride were added, and the mixture was reacted at 55° C. for 3 hours. After dialysis and drying, double-bond carboxymethyl chitosan was obtained;

[0049] Step (2): 0.3 parts of epoxy-terminated silicone oil and 1.2 parts of isopropanol are mixed evenly, 0.009 parts of N-aminoethyl-3-aminopropyltriethoxysilane are added, and the mixture is reacted at 45°C for 1 hour. 0.0045 parts of ethyl orthosilicate, 0.0045 parts of hexadecanetriethoxysilane and 0.0135 parts of deionized water are added, and the reaction is continued for 2 hours. The mixture is heated to 70°C, 0.3 parts of double-bond carboxymethyl chitosan and 0.03 parts of tetrabutylammonium bromide are added, and the reaction is continued for 4 hours. The mixture is cooled to 45°C, 0.45 parts of sodium hydroxide are added, and the reaction is continued for 2 hours. After washing and distillation under reduced pressure, a double-bond compound is obtained.

[0050] Step (3): 0.1 parts of octylphenol polyoxyethylene ether, 0.02 parts of alcohol ether carboxylate and 5 parts of deionized water are mixed evenly, 0.2 parts of styrene, 0.2 parts of butyl acrylate, 0.4 parts of methyl methacrylate and 0.1 parts of acrylic acid are added, and the mixture is stirred for 20 minutes. The pH value of the system is adjusted to 8 using a sodium hydroxide solution, and the mixture is heated to 70°C, and 0.8 parts of a 2 wt% aqueous initiator solution is added dropwise, and the mixture is dripped over a period of 40 minutes. The mixture is kept warm for reaction for 1 hour, and the mixture is cooled to 50°C, and 0.3 parts of a double bond-containing compound are added, and the mixture is kept warm for reaction for 0.5 hours to obtain a waterproofing agent.

[0051] Embodiment 2: A method for preparing a building material containing waste, comprising the following process:

[0052] 20 parts of fly ash, 45 parts of slag powder, 20 parts of CFB slag, 15 parts of red mud and 0.07 parts of grinding aid are mixed evenly to obtain a mineral admixture; 20 parts of mineral admixture, 35 parts of steel slag powder, 20 parts of tailings sand and 15 parts of carbide slag are mixed evenly, and 30 parts of desulfurized gypsum, 12 parts of phosphogypsum, 0.8 parts of composite fiber and 12 parts of water are added and mixed evenly to obtain a mixture; the mixture and 0.08 parts of water retaining agent, 0.8 parts of redispersible latex powder, 0.2 parts of water reducing agent, 0.3 parts of air entraining agent and 0.5 parts of waterproofing agent are mixed evenly to obtain a building material containing waste;

[0053] The preparation method of the composite fiber is as follows:

[0054] Step S1: 0.2 parts of 16 mol / L concentrated nitric acid, 2.2 parts of deionized water and 0.09 parts of ammonium cerium nitrate are mixed evenly to obtain an acidic ammonium cerium nitrate solution; 14 parts of deionized water, 0.4 parts of polyvinyl alcohol fiber and 0.96 parts of glycidyl methacrylate are mixed evenly, 1.64 parts of the acidic ammonium cerium nitrate solution are added dropwise for 40 minutes, the mixture is reacted at 45° C. for 5 hours, and after filtering, washing and drying, epoxidized polyvinyl alcohol fiber is obtained;

[0055] Step S2: heating 0.6 parts of basalt fiber at 280° C. for 1.5 hours, cooling to room temperature, soaking in an acetone solution for 1.5 hours, washing and drying to obtain pretreated basalt fiber; mixing 0.6 parts of pretreated basalt fiber and 6.6 parts of anhydrous ethanol, 1.5 parts of deionized water, and 0.18 parts of 3-aminopropyltrimethoxysilane evenly, adding 0.12 parts of nano-silicon dioxide, reacting at 60° C. for 5 hours, filtering, washing, and drying to obtain amino basalt fiber;

[0056] Step S3: 0.4 parts of epoxidized polyvinyl alcohol fiber, 0.6 parts of amino basalt fiber and 2 parts of tetrahydrofuran were mixed evenly, reacted for 5 hours, filtered, washed and dried to obtain composite fibers;

[0057] The preparation method of the waterproofing agent is as follows:

[0058] Step (1): 0.8 parts of carboxymethyl chitosan and 32 parts of deionized water were mixed evenly, 0.09 parts of methacrylic anhydride were added, and the mixture was reacted at 60° C. for 4 hours. After dialysis and drying, double-bond carboxymethyl chitosan was obtained;

[0059] Step (2): 0.5 parts of epoxy-terminated silicone oil and 2.5 parts of isopropanol are mixed evenly, 0.02 parts of N-aminoethyl-3-aminopropyltriethoxysilane are added, and the mixture is reacted at 50°C for 2 hours. 0.012 parts of ethyl orthosilicate, 0.0168 parts of hexadecanetriethoxysilane and 0.042 parts of deionized water are added, and the reaction is continued for 3 hours. The mixture is heated to 75°C, 0.75 parts of double-bond carboxymethyl chitosan and 0.1 parts of tetrabutylammonium bromide are added, and the reaction is continued for 5 hours. The mixture is cooled to 50°C, 0.9 parts of sodium hydroxide are added, and the reaction is continued for 2.5 hours. After washing and distillation under reduced pressure, a double-bond compound is obtained.

[0060] Step (3): 0.1 parts of octylphenol polyoxyethylene ether, 0.024 parts of alcohol ether carboxylate and 5.5 parts of deionized water are mixed evenly, 0.25 parts of styrene, 0.375 parts of butyl acrylate, 0.625 parts of methyl methacrylate and 0.2 parts of acrylic acid are added, and the mixture is stirred for 25 minutes. The pH value of the system is adjusted to 9 using a sodium hydroxide solution, the mixture is heated to 75°C, 1.25 parts of a 3 wt % aqueous initiator solution are added dropwise, and the mixture is dripped over a period of 50 minutes. The mixture is kept warm for reaction for 1.5 hours, the mixture is cooled to 55°C, 0.5 parts of a double bond-containing compound are added, and the mixture is kept warm for reaction for 0.8 hours to obtain a waterproofing agent.

[0061] Embodiment 3: A method for preparing a building material containing waste, comprising the following process:

[0062] 25 parts of fly ash, 50 parts of slag powder, 25 parts of CFB slag, 20 parts of red mud and 0.08 parts of grinding aid are mixed evenly to obtain a mineral admixture; 25 parts of mineral admixture, 40 parts of steel slag powder, 25 parts of tailings sand and 20 parts of carbide slag are mixed evenly, and 35 parts of desulfurized gypsum, 15 parts of phosphogypsum, 1.0 parts of composite fiber and 15 parts of water are added and mixed evenly to obtain a mixture; the mixture and 0.10 parts of water retaining agent, 1.0 parts of redispersible latex powder, 0.3 parts of water reducing agent, 0.5 parts of air entraining agent and 0.8 parts of waterproofing agent are mixed evenly to obtain a building material containing waste;

[0063] The preparation method of the composite fiber is as follows:

[0064] Step S1: 0.2 parts of 16 mol / L concentrated nitric acid, 2.4 parts of deionized water and 0.1 parts of cerium ammonium nitrate are mixed evenly to obtain an acidic nitric acid solution; 14.4 parts of deionized water, 0.4 parts of polyvinyl alcohol fiber and 1 part of glycidyl methacrylate are mixed evenly, 1.68 parts of the acidic nitric acid solution are added dropwise for 50 minutes, the reaction is carried out at 50° C. for 6 hours, and after filtering, washing and drying, epoxidized polyvinyl alcohol fiber is obtained;

[0065] Step S2: heating 0.8 parts of basalt fiber at 300° C. for 2 hours, cooling to room temperature, soaking in an acetone solution for 2 hours, washing and drying to obtain pretreated basalt fiber; mixing 0.8 parts of pretreated basalt fiber and 9.6 parts of anhydrous ethanol, 2.4 parts of deionized water, and 0.32 parts of 3-aminopropyltrimethoxysilane evenly, adding 0.08 parts of nano-silicon dioxide, reacting at 65° C. for 6 hours, filtering, washing, and drying to obtain amino basalt fiber;

[0066] Step S3: 0.4 parts of epoxidized polyvinyl alcohol fiber, 0.8 parts of amino basalt fiber and 2.4 parts of tetrahydrofuran were mixed evenly, reacted for 6 hours, filtered, washed and dried to obtain composite fiber;

[0067] The preparation method of the waterproofing agent is as follows:

[0068] Step (1): 1.6 parts of carboxymethyl chitosan and 80 parts of deionized water were mixed evenly, 0.32 parts of methacrylic anhydride were added, and the mixture was reacted at 65° C. for 5 h. After dialysis and drying, double-bond carboxymethyl chitosan was obtained;

[0069] Step (2): 0.8 parts of epoxy-terminated silicone oil and 4.8 parts of isopropanol are mixed evenly, 0.04 parts of N-aminoethyl-3-aminopropyltriethoxysilane are added, and the mixture is reacted at 55°C for 3 hours, 0.028 parts of ethyl orthosilicate, 0.042 parts of hexadecanetriethoxysilane and 0.112 parts of deionized water are added, and the reaction is continued for 4 hours, the temperature is raised to 80°C, 1.6 parts of double-bond carboxymethyl chitosan and 0.24 parts of tetrabutylammonium bromide are added, the reaction is continued for 6 hours, the temperature is lowered to 55°C, 1.6 parts of sodium hydroxide are added, the reaction is continued for 3 hours, and a double-bond compound is obtained after washing and distillation under reduced pressure;

[0070] Step (3): octylphenol polyoxyethylene ether, alcohol ether carboxylate and deionized water are mixed evenly, 0.32 parts of styrene, 0.64 parts of butyl acrylate, 0.96 parts of methyl methacrylate and 0.32 parts of acrylic acid are added, and stirred for 30 minutes. The pH value of the system is adjusted to 10 with sodium hydroxide solution, and the temperature is raised to 80°C. 1.92 parts of 5wt% initiator aqueous solution are added dropwise, and the dripping is completed within 60 minutes. The reaction is kept warm for 2 hours, and the temperature is lowered to 60°C. 0.8 parts of a double bond-containing compound are added, and the reaction is kept warm for 1.0 hour to obtain a waterproofing agent.

[0071] Comparative Example 1: A building material containing waste and a preparation method thereof, comprising the following processes:

[0072] Compared with Example 2, the comparative example 1 does not add the composite fiber, and the other steps are the same as those of Example 2.

[0073] Comparative Example 2: A building material containing waste and a preparation method thereof, comprising the following processes:

[0074] Compared with Example 2, the waterproofing agent in Comparative Example 2 is replaced with sodium methyl silicate of the same mass (sourced from Jinan Xingfeilong Chemical Co., Ltd.), and the other steps are the same as those in Example 2.

[0075] Comparative Example 3: A building material containing waste and a preparation method thereof, comprising the following processes:

[0076] Compared with Example 2, no mineral admixture is added in Comparative Example 3, and other steps are the same as those in Example 2.

[0077] Comparative Example 4: A building material containing waste and a preparation method thereof, comprising the following processes:

[0078] The preparation method of the waterproofing agent is as follows:

[0079] Step (1): 0.8 parts of carboxymethyl chitosan and 32 parts of deionized water were mixed evenly, 0.09 parts of methacrylic anhydride were added, and the mixture was reacted at 60° C. for 4 hours. After dialysis and drying, double-bond carboxymethyl chitosan was obtained;

[0080] Step (2): 0.5 parts of epoxy-terminated silicone oil and 2.5 parts of isopropanol are mixed evenly, 0.05 parts of N-aminoethyl-3-aminopropyltriethoxysilane are added, and the mixture is reacted at 50°C for 2 hours. 0.012 parts of ethyl orthosilicate, 0.0168 parts of hexadecanetriethoxysilane and 0.042 parts of deionized water are added, and the reaction is continued for 3 hours. The mixture is heated to 75°C, 0.75 parts of double-bond carboxymethyl chitosan and 0.1 parts of tetrabutylammonium bromide are added, and the reaction is continued for 5 hours. The mixture is cooled to 50°C, 0.9 parts of sodium hydroxide are added, and the reaction is continued for 2.5 hours. After washing and distillation under reduced pressure, a double-bond compound is obtained.

[0081] Step (3): 0.1 parts of octylphenol polyoxyethylene ether, 0.024 parts of alcohol ether carboxylate and 5.5 parts of deionized water are mixed evenly, 0.25 parts of styrene, 0.375 parts of butyl acrylate, 0.625 parts of methyl methacrylate and 0.2 parts of acrylic acid are added, and the mixture is stirred for 25 minutes. The pH value of the system is adjusted to 9 using a sodium hydroxide solution, the mixture is heated to 75°C, 1.25 parts of a 3 wt% initiator aqueous solution are added dropwise, the mixture is dripped over a period of 50 minutes, the mixture is kept warm for reaction for 1.5 hours, the mixture is cooled to 55°C, 0.5 parts of a double bond-containing compound are added, the mixture is kept warm for reaction for 0.8 hours, and a waterproofing agent is obtained;

[0082] Compared with Example 2, the mass ratio of the terminal epoxy silicone oil and N-aminoethyl-3-aminopropyltriethoxysilane in Comparative Example 4 is 1:0.1; the other steps are the same as those in Example 2.

[0083] Experiment: The flexural strength and compressive strength were determined according to GB / T 28627-2023 "Plastering Gypsum". The experimental steps were as follows: the waste-containing building materials obtained in Examples 1-3 and Comparative Examples 1-4 were injected into a 40 mm×40 mm×160 mm mold. After standard curing for 28 days, a sample was obtained and tested using a DCS-R-1 million mechanical testing machine. Water resistance test: The waste-containing building materials obtained in Examples 1-3 and Comparative Examples 1-4 were injected into a 40 mm×40 mm×40 mm mold. After standard curing for 7 days, a sample was obtained. The sample was dried in an oven to constant mass at a temperature of 42°C, its mass was weighed and marked as A1, and then it was soaked in tap water at room temperature for 2 hours, and the mass was taken out and marked as A2. The water absorption rate was calculated as: (A2-A1) / A1×100%.

[0084] The test results are shown in Table 1:

[0085] Table 1: Performance tests of building materials containing waste in Examples 1-3 and Comparative Examples 1-4

[0086]

[0087] According to the data in the above table, we can clearly draw the following conclusions:

[0088] 1. Compared with Examples 1-3, the flexural strength and compressive strength of the product obtained in Comparative Example 1 decreased, indicating that the addition of composite fibers in the present invention can enhance the mechanical properties of the material.

[0089] 2. Compared with Examples 1-3, the water absorption rate of the product obtained in Comparative Example 2 increases, which shows that compared with sodium methyl silicate, the waterproofing agent prepared by the present invention has better waterproof effect and can improve the water resistance of the material; the flexural strength and compressive strength of the product obtained in Comparative Example 3 decrease, which shows that the addition of mineral admixtures in the present invention can improve the structural strength of the material while ensuring good processability.

[0090] 3. Compared with Examples 1-3, the water resistance of the product obtained in Comparative Example 4 is reduced, indicating that adding too much N-aminoethyl-3-aminopropyltriethoxysilane will cause the epoxy groups of the terminal epoxy silicone oil to react completely, thereby affecting the subsequent reactions and ultimately resulting in a decrease in the waterproof effect.

[0091] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0092] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A building material containing waste, characterized in that: The invention comprises the following components by weight: 25-35 parts of desulfurized gypsum, 10-15 parts of phosphogypsum, 15-25 parts of mineral admixture, 30-40 parts of steel slag powder, 15-25 parts of tailings sand, 10-20 parts of carbide slag, 0.2-1.0 parts of composite fiber, 0.3-0.8 parts of waterproofing agent, 0.05-0.10 parts of water retaining agent, 0.5-1.0 parts of redispersible latex powder, 0.1-0.3 parts of water reducing agent, 0.1-0.5 parts of air entraining agent and 10-15 parts of water; The preparation method of the composite fiber is as follows: Step S1: evenly mix concentrated nitric acid, deionized water and ammonium cerium nitrate to obtain an acidic ammonium cerium nitrate solution; evenly mix deionized water, polyvinyl alcohol fiber and glycidyl methacrylate, dropwise add the acidic ammonium cerium nitrate solution for 30-50 minutes, react at 40-50° C. for 4-6 hours, filter, wash and dry to obtain epoxidized polyvinyl alcohol fiber; Step S2: heating the basalt fiber at 250-300° C. for 1-2 hours, cooling to room temperature, soaking in an acetone solution for 1-2 hours, washing and drying to obtain pretreated basalt fiber; uniformly mixing the pretreated basalt fiber with anhydrous ethanol, deionized water and 3-aminopropyltrimethoxysilane, adding nano-silica, reacting at 55-65° C. for 4-6 hours, filtering, washing and drying to obtain amino basalt fiber; Step S3: uniformly mixing the epoxidized polyvinyl alcohol fiber, the amino basalt fiber and tetrahydrofuran, reacting for 4-6 hours, filtering, washing and drying to obtain composite fibers; The preparation method of the waterproofing agent is as follows: Step (1): mix carboxymethyl chitosan and deionized water evenly, add methacrylic anhydride, react at 55-65° C. for 3-5 hours, dialyze and dry to obtain double-bond carboxymethyl chitosan; Step (2): Evenly mix the epoxy-terminated silicone oil and isopropanol, add N-aminoethyl-3-aminopropyltriethoxysilane, react at 45-55°C for 1-3h, add ethyl orthosilicate, hexadecanetriethoxysilane and deionized water, continue to react for 2-4h, heat to 70-80°C, add double-bond carboxymethyl chitosan and tetrabutylammonium bromide, react for 4-6h, cool to 45-55°C, add sodium hydroxide, continue to react for 2-3h, wash and distill under reduced pressure to obtain a double bond-containing compound; Step (3): uniformly mix octylphenol polyoxyethylene ether, alcohol ether carboxylate and deionized water, add styrene, butyl acrylate, methyl methacrylate and acrylic acid, stir for 20-30 minutes, adjust the system pH to 8-10 with sodium hydroxide solution, heat to 70-80°C, drip initiator aqueous solution, drip for 40-60 minutes, keep warm for reaction for 1-2 hours, cool to 50-60°C, add double bond-containing compound, keep warm for reaction for 0.5-1.0 hours, and obtain a waterproofing agent.

2. The waste-containing building material according to claim 1, characterized in that: The mineral admixture comprises the following components by weight: 25-35 parts of fly ash, 40-50 parts of slag powder, 15-25 parts of CFB slag, 10-20 parts of red mud, and 0.05-0.08 parts of grinding aid.

3. The waste-containing building material according to claim 1, characterized in that: In the step S3, the mass ratio of the epoxidized polyvinyl alcohol fiber to the amino basalt fiber is 1:(1-2).

4. The waste-containing building material according to claim 1, characterized in that: In the step (2), the mass ratio of the epoxy-terminated silicone oil, the double-bond carboxymethyl chitosan, the tetrabutylammonium bromide and the sodium hydroxide is 1: (1-2): (0.1-0.3): (1.5-2.0).

5. The waste-containing building material according to claim 1, characterized in that: The water retaining agent is hydroxypropyl methylcellulose ether.

6. The waste-containing building material according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

7. The waste-containing building material according to claim 1, characterized in that: The air entraining agent is a sodium rosin acid air entraining agent.

8. The method for preparing a waste-containing building material according to any one of claims 1 to 7, characterized in that: The steps include: The mineral admixture, steel slag powder, tailings sand and carbide slag are mixed evenly, and desulfurized gypsum, phosphogypsum, composite fiber and water are added and mixed evenly to obtain a mixture; the mixture and a water retaining agent, a dispersant, a water reducing agent, an air entraining agent and a waterproofing agent are mixed evenly to obtain a building material containing waste.

Citation Information

Patent Citations

  • Geopolymer-based artificial flood control stone prepared from all wastes and preparation method thereof

    CN110668772A

  • PVA fiber reinforced cement-based composite material

    CN112624679A